The spatial convergence or the divergence of the feminization of the demographic old age in Poland? - Podogrodzka, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In the article based on information from the years 1991–2011 the following hypotheses were subjected to the verification: 1. with time, we observe spatial standardizing of coefficient rate of the feminization of the demographic old age; 2. the spatial image of the rate of the feminization of the demographic old age did not undergo the change over time; 3. with time, the increases in the rate of the feminization of the demographic old age are more distinct in these areas, where its value was relatively high at the beginning of the analyzed period; 4. Different measures describing the spatial feminization of the demographic old age are leading to similar conclusions in the evaluation of its spatial convergence. Not all of the put forward theses were confirmed.